Explaining cross-border large-value payment flows: evidence from TARGET and EURO 1 data - Simonetta Rosati; Stefania Secola (European Central Bank (ECB), 2005)
We analyse the distribution of the TARGET cross-border interbank payment flows, from both a cross-section and time series point of view, using average daily data for the period 1999-2002. We find out that first, “location matters”, in the sense that bilateral payment flows seem to reflect an organisation of interbank trading between countries whereby the size of the banking sectors, geographical proximity and cultural similarities play a significant role. This result is confirmed also by a model developed drawing on the gravity models literature. Second, we find that the payment traffic in TARGET is strongly affected by market technical deadlines. In addition, such traffic is positively related mainly to the liquidity conditions and to the turnover of the euro area money market, (particularly the unsecured overnight segment). Our model also provides a good explanation of the determinants of the interbank payments settled in the EURO 1 system.
Keywords: E58; G20; G21; 330; EURO 1; euro area interbank market; location; payment systems; TARGET; Internationaler Zahlungsverkehr; Gravitationsmodell; Schätzung; Eurozone; EU-Staaten